A Framework for Value Creation through Human Resource Management in Transportation Platforms - Mohammad Saeid Almaspour; Hamze Khastar; Saeid Jafarinia; Bijan Abdollahi (مطالعات منابع انسانی, 2021)
Background & Purpose: Due to growth and development of transportation platforms in recent years and the growing importance of human resources, it is essential to investigate the way to create value through human resource management in this new form of business. The purpose of this study is to determine the values ​​of stakeholders and the way to create value through human resource management in transportation platform businesses for stakeholders.Methodology: Sequential mixed method was used in the present research. This research has been conducted in two main phases. In the first stage, using literature and thematic analysis method, a list of stakeholders’ values ​​was identified. Then, a sample of stakeholders from two famous Iranian transportation platforms were asked to rate the extracted values using an open-ended questionnaire. In phase two, an interview was performed with a group of experts who were purposefully selected. The value creation capabilities of the platforms and the way to create value through human resource management in the transportation platforms were identified via the thematic analysis.Findings: In this study, 12 values considered by the main stakeholders in transportation platforms, two value creation capabilities (electronic processes management, information management), and two value creation methods (improving work planning and control system efficiency) were extracted through human resource management.Conclusion: By creating a framework consisting of value creation capabilities, value creation methods, and stakeholders’ values, findings can be used in better understanding and more effective use of human resource management so as to create more and more values for stakeholders in transportation platforms. Using this results, practical recommendations for managers and operators as well as suggestions for future research are provided.